From Boulanger to Stockhausen interviews and a memoir - Varga, Bálint AndrásXXeinterviewer (Boydell & Brewer, 2013)
Bálint András Varga makes available here twenty-one extended interviews with some of the most notable figures in music from the past fifty years, as well as lively "snippets" from interviews Varga conducted with thirteen other equally renowned musicians. The interviewees include singers Elisabeth Schwarzkopf and Cathy Berberian; pianists Alfred Brendel and Arthur Rubinstein, violinists Isaac Stern and Yehudi Menuhin; conductors Claudio Abbado and Sir Neville Marriner; composers György Ligeti, and Karlheinz Stockhausen; and legendary pedagogue Nadia Boulanger. Of special interest is an interview with the reclusive composer György Kurtág, here published for the first time in any language. From Boulanger to Stockhausen concludes with a touching memoir by Varga of his experiences growing up in a Jewish family in Hungary during World War II and the early years of Communist rule. Varga's recollections also include details about how he managed to interview so many remarkable musicians-thanks in large part to his employment at the Hungarian state radio station and then in the music-publishing industry, which brought him to, among other places, London and Vienna, where he now lives. Bálint András Varga has spent nearly forty years working for and with composers. His previous books for the University of Rochester Press are György Kurtág: Three Interviews and Ligeti Homages and Three Questions for Sixty-Five Composers